Testing of stainless steel I-section columns in fire. (15th January 2021) - Xing, Zhe; Zhao, Ou; Kucukler, Merih; Gardner, Leroy
Highlights: Structural behaviour of stainless steel I-section columns in fire is investigated. Eight fire tests on austenitic stainless steel I-section columns are carried out. Complementary room temperature column buckling tests are also described. EN 1993-1-2 and Kucukler et al.'s proposal are assessed against experimental results. Abstract: Although there have been significant developments in the testing, simulation and design of stainless steel structural elements at room temperature, the structural response of stainless steel members in fire has received significantly less attention. In particular, full-scale fire tests on stainless steel I-section members, which are becoming increasingly widely used in structural engineering applications to meet growing load-carrying capacity demands, are currently scarce. In this paper, the results of eight full-scale anisothermal fire tests on grade 1.4301 laser-welded austenitic stainless steel I-section columns are reported. Complementary initial local and global geometric imperfection measurements, room temperature tensile coupon tests and room temperature column buckling tests are also described. On the basis of the findings from the fire experiments, the accuracy and safety of the European fire design standard EN 1993-1-2 and the recent design recommendations of Kucukler et al. [1] for stainless steel columns in fire, which will be incorporated into the upcoming version of EN 1993-1-2, are assessed. It is observed that, relative to the existing column fire design rules in EN 1993-1-2, the design method of Kucukler et al. [1] provides more reliable ultimate strength predictions for austenitic stainless steel I-section columns in fire.